Neurodiversity and Artistic Performance Characteristic of Children With Autism Spectrum Disorder - Masataka, Nobuo (Frontiers in Psychology, 2018)
Neurodiversity refers to the notion that seemingly ‘impaired’ cognitive as well as emotional features characteristic of developmental disorders such as autism spectrum disorder (ASD) fall into normal human behavioral variations that should enjoy some selective advantages. In the present experiment, the author compared what was depicted in subjects’ drawings after they experienced an identical event, e.g., going on a picnic to a garden in the vicinity of their nursery school, between children with ASD and IQ-matched, typically developing (TD) children. When the material was coded according to types of drawn objects, such as human, animal, plant, food, vehicle, building, and others, the overall variability of the objects did not differ between TD children and children with ASD. However, TD children were more likely than children with ASD to depict human images. Conversely, other objects were more likely to be drawn by children with ASD than by TD children. While TD children were more likely to focus on humans than on nonhuman objects when drawing, children with ASD were more likely to focus on nonhuman objects than on humans even after both had experienced an identical event. The author argues that such findings are empirical evidence for the claim that there is some selective advantage of enhanced capabilities characteristic of ASD, i.e., neurodiversity, that may represent a balance toward ''folk physics'' at the expense of ''folk psychology''.